INTERNAL FOCALIZATION OF CHARACTERS IN FRANKENSTEIN BY MARY SHELLEY - Nurjaya, Muhammad Luthfi; Juanda, Juanda (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This research analyses the internal focalization of characters in the novel Frankenstein by Mary Shelley. Based on narratology, focalization can be divided into three kind zero focalization, internal focalization and external focalization. Internal focalization is when narrator knows what character thoughts, they cannot explain the thought of others character. Frankenstein by Mary Shelley told us about the story about a man named Victor Frankenstein who created monster and brought that back to life. After that Victor was terrorized by the monster and ruin his life. The story mostly uses internal focalization as every character told the story through their perspective. This paper uses a qualitative method. The data are collected and represented in direct quotes from the book. The theory that is used in this research is based on Gérard Genette's theory about narratology, which is provide the information about how the story is told based on narrator. The research reveals that Mary Shelley uses more than one internal focalization in Frankenstein. The first is coming from Captain Walton to Victor Frankenstein to the monster and come back to Victor and ended with Captain Walton. The shifts point of view in internal focalization shows others character perspective about how the story goes.